Islamic ethnomethodology study: constructing Binthe Biluhuta accounting practices based on Gorontalo Local Wisdom - Thalib, Mohamad Anwar; Mohamad, Roni; Syawaluddin; Koni, Wiwin; Gobel, Yulia Puspitasari (Accounting Research Institute (ARI), Universiti Teknologi MARA, Shah Alam, 2025)
This research stemmmed from the gap between the dominance of theories and studies on accounting that lack local values, leading to the increasing marginalization of local wisdom behind accounting practices. This study aimed to construct binthe biluhuta accounting practices based on the local cultural values of the Gorontalo people in Indonesia. The approach used was Islamic ethnomethodology. The method used was qualitative. There were five informants. The type of data analysis was descriptive with five stages of data analysis, namely charity, knowledge, faith, information revelation, and courtesy. Research results showed that value-based capital accounting practices delo huhebu. The implications of this research are local wisdom values found in binthe biluhuta accounting practices can combine capital accounting theory to make it more holistic. When building a business, sellers can use the binthe biluhuta accounting concept with a materialist, humanist, and spiritual soul. The novelty of this research is it presents accounting practices by binthe biluhuta sellers based on the local wisdom values of the Gorontalo people, which has never been raised before in accounting research.